2018
DOI: 10.3920/bm2017.0104
|View full text |Cite
|
Sign up to set email alerts
|

Effect of tablets containing probiotic candidate strains on gingival inflammation and composition of the salivary microbiome: a randomised controlled trial

Abstract: The aim of the study was to investigate clinical and microbial effects of probiotic candidate strains in patients with moderate gingivitis. The null hypothesis was that the clinical measurements with treatment would not differ from placebo. 47 adult patients were enrolled in a randomised placebo-controlled trial with a 4-week intervention of tablets containing a mix of Lactobacillus rhamnosus PB01, DSM 14869 and Lactobacillus curvatus EB10, DSM 32307 or placebo. Clinical examinations and samplings were done at… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
81
0

Year Published

2019
2019
2022
2022

Publication Types

Select...
3
3

Relationship

0
6

Authors

Journals

citations
Cited by 43 publications
(86 citation statements)
references
References 30 publications
5
81
0
Order By: Relevance
“…In almost 50% of the included studies, clinical periodontal inflammatory parameters showed significant improvements in the test group as compared to control group at follow‐up. Five studies reported comparable clinical inflammatory parameters between test and control groups at follow‐up …”
Section: Resultsmentioning
confidence: 96%
See 4 more Smart Citations
“…In almost 50% of the included studies, clinical periodontal inflammatory parameters showed significant improvements in the test group as compared to control group at follow‐up. Five studies reported comparable clinical inflammatory parameters between test and control groups at follow‐up …”
Section: Resultsmentioning
confidence: 96%
“…From these 25 articles, 15 studies were subsequently eliminated. The final stage of selection yielded 10 articles to be included and were therefore processed for data extraction ( ĸ : 0.94 [0.89–0.99]) . The selected studies were conducted at university hospitals.…”
Section: Resultsmentioning
confidence: 99%
See 3 more Smart Citations